Grandma Lim's Persimmons - Bhamray, Sunita Lad (2013)
Grandma Lim liked to grow persimmons in her garden. One day she saw a beautiful persimmon on a tree. When it was ripe, she would give the persimmon to her granddaughter Mei Ling, she thought. But before she could do that, the persimmon disappeared. That's when three friends pitched in to help.